АНАРХІСТСЬКІ СУБКУЛЬТУРНІ СПІЛЬНОТИ ЯК СУБ’ЄКТ ЛІВОГО РАДИКАЛІЗМУ В УКРАЇНІ. - Є. О., Васильчук (Hileya: Scientific Bulletin / Gileya, 2025)
The peculiarities of the functioning of anarchist subcultural communities as a subject of left-wing radicalism in Ukraine are analyzed. It is concluded that the existence of a significant number of anarchist tendencies in Ukraine indicates primarily not the «vitality» of this ideological doctrine in general, but the relative popularity in the youth environment of libertarian ideas that combine individual worldview principles of anarchism, countercultural products and ideas of a number of Western European left-wing radical philosophers